2020
DOI: 10.1007/s40830-020-00299-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Small-Scale Shape Memory Oxides

Abstract: This review presents an overview of the developments in small-scale shape memory materials: from alloys to oxides and ceramics. Shape memory oxides such as zirconia, different ferroelectric perovskites and VO2-based materials have favorable characteristics of high strength, high operating temperature and chemical resistance, which make this class of shape memory materials interesting for special applications, e.g., in harsh environments or at the nanoscale. Because of the constraint and mismatch stress from ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Shape-memory alloys (SMAs) have been widely explored as actuating materials because of their large deformation capability caused by reversible martensitic phase transformations. However, their application at the nanoscale is highly constrained because martensitic phase transformations are suppressed below a critical size (~50 nm) 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Shape-memory alloys (SMAs) have been widely explored as actuating materials because of their large deformation capability caused by reversible martensitic phase transformations. However, their application at the nanoscale is highly constrained because martensitic phase transformations are suppressed below a critical size (~50 nm) 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion-strengthened copper alloys that have been dispersion-strengthened are used to make copper-based matrix composites [3][4][5][6]. Wang et al [7] had shown some oxides can exhibit exceptional shape memory effects and superelasticity at nano/microscales, as evidenced by recent development in shape memory oxide studies connected to small-scale approaches such as lowering grain boundaries, strain engineering, and use in the form of nanoscale thin films. The shape memory efficiency of the materials systems ZrO 2 , BiFO 3 , and VO 2 in bulk and small-scale is reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Ludwig presented comparisons between shape memory alloys (SMAs) and shape memory oxides ceramics to show that by small‐scale application of SMCs, the constraints of phase transformation are minimized and even higher work density than SMAs are achievable. [ 26 ] Elastic properties of the matrix crystal and microstructural features such as precipitates are important factors affecting the transformation temperatures. [ 27 ] To understand the intrinsic parameters that control the transformation temperatures in metallic SMAs, Zarinejad suggested the need to acquire in depth knowledge of how the atomic bonding strength of the matrix crystal in shape memory material can be influenced by its chemical composition.…”
Section: Introductionmentioning
confidence: 99%